Receiving Nicaea: On Creeds, Culture, and Christian Witness - Mandla, Vincent Nkosinathi (Stellenbosch Theological Journal, 2026)
This research identifies the most innovative aspects within the new post-Cold War and post-apartheid context of African theology, suggesting that theology plays a vital role in recognising, valuing, interpreting, and empowering the agency of African Christians as they confront cultural, religious, and economic challenges in their everyday lives. This is in light of Africa’s contribution to Christianity through the theological schools and churches of Alexandria, Carthage and Ethiopia, through a pivotal role they played in theological perspectives that became instrumental in developing a foundational doctrine “One Faith” in Nicaea, 325 AD. Focusing on the renewed acknowledgement of African agency, African theologians strive to develop a more harmonious and less conflicted connection between Africa and Christianity, as well as between Africans and their difficult Christian/church history through liberative theology and decoloniality. The role of a liberative paradigm is an impetus not only to global solidarity but also to church solidarity and unity. The Nicene creed has tenets of unity, theological convictions and peace, and the question this research will pose is whether Western theology, considering its past in the Third World share the same Christian convictions of unity beyond theological theory but as praxis in Africa?